Catalytic steam reforming of biomass tar using iron catalysts - Min, Zhenhua (Curtin University, 2010)
Biomass has become an increasingly important renewable source of energy forenhanced energy security and reduced CO[subscript]2 emissions. Gasification is at the core of many biomass utilisation technologies for such purposes as the generation of electricity and the production of hydrogen, liquid fuels and chemicals. However, gasification faces a number of technical challenges to become a commercially feasible renewable energy technology. The most important one is the presence of tar in the gasification product gas. The ultimate purpose of this thesis was to investigate the catalytic reforming of tar using cheap catalysts as an effective means of tar destruction.In this thesis, natural ilmenite ore and novel char-supported catalysts were studied as catalysts for the steam reforming of biomass tar derived from the pyrolysis of mallee biomass in situ in two-stage fluidised-bed/fixed-bed quartz reactors. In addition to the quantification of tar conversion, the residual tar samples were also characterised with UV-fluorescence spectroscopy. Both fresh and spent catalysts were characterised with X-ray diffraction spectroscopy, FT-Raman spectroscopy and thermogravimetric analysis.The results indicate that ilmenite has activity for the reforming of tar due to its highly dispersed iron-containing species. Both the externally added steam and low concentration oxygen affect the tar reforming on ilmenite significantly. The properties of biomass affect the chemical composition of its volatiles and therefore their reforming with the ilmenite catalyst. Compared with sintering, coke deposited on ilmenite is the predominant factor for its deactivation.During the steam reforming process, the char-supported iron/nickel catalysts exhibit very high activity for the reforming of tar. In addition, NO[subscript]x precursors could be decomposed effectively on the char-supported iron catalyst during the steam reforming process. The hydrolysis of HCN and the decomposition of NH[subscript]3 on the catalyst are the key reactions for the catalytic destruction of NO[subscript]x precursors.The kinetic compensation effects demonstrate that the reaction pathways on the char-supported catalysts are similar but different from those on ilmenite. The proprieties of catalyst support could play important roles for the activities of the catalysts and the reaction pathways on the catalysts. The char support as part of the char-supported catalysts can undergo significant structural changes during the catalytic reforming of biomass volatiles.